Tasks Over Traits : User perception of humanlike features in goal-oriented chatbots - Haresamudram, Kashyap; van As, Nena; Larsson, Stefan (International Journal of Human-Computer Interaction, 2025)
Chatbots designed to achieve specific goals are increasingly used in service roles. Human-like characteristics in chatbots are seen as beneficial to interaction. Given the purpose-driven nature of goal-oriented chatbots, whether humanlikess of various characteristics of these chatbots has an effect on their perception and use is unclear. This study explores the role of humanlikeness in goal-oriented chatbots through three experiments focused on agent behavior, interaction modality, and communication medium in a travel-assistant context. The findings suggest that while human-like behavioral attributes enhance perceptions of anthropomorphism, animacy, and likeability, they do not significantly affect reliability, perceived intelligence, or safety. The text medium was also perceived as more trustworthy and anthropomorphic than the voice medium. Overall, successful task completion seems to be the most crucial factor in shaping user perceptions, suggesting that humanlikeness may be less critical in goal-oriented chatbot interactions.
Keywords: chatbots; interaction; human-like; goal-oriented chatbots; anthropomorphic; trustworthiness; user perception; humanlikeness